Sustainable property development: a challenge - Yusoff, Mohd Nazaruddin; Abadi, Hooman; Talib, Azlizan; Mohd Nawi, Mohd Nasrun; Salleh, Nurul Azita; Mydin, Md Azree Othuman (DIVA ENTERPRISES PVT. LTD.., 2018)
Sustainability development is a continuous economic development approach strategy which needs to conserve local surrounding and enhance quality of life. Sustainable development will enable the economic progress and the natural quality achieved the goals of continuous human welfare. If the sustainable development strategies had been practiced seriously, it will able to preserve the environment, saving the resources, increasing the local business growth and making the community less vulnerable to the pollution threats. This paper recommends the need for all parties involved to develop plans and practice in sustainability concept and design in property development in this country as a whole.